Forensic uses of digital imaging - Russ, John C. (CRC Press, Taylor & Francis Group, 2016)
The ability to work with, and retrieve images, is vital to forensic and criminal case work. During a five-decade-long career, author John C. Russ has taught methods for image processing and measurement to thousands of students and workshop material to present the information most relevant to forensic science.